Effects of Computer-Based Intervention Through Acoustically Modified Speech (Fast ForWord) in Severe Mixed Receptive-Expressive Language Impairment: Outcomes From a Randomized Controlled Trial. - Cohen, Wendy; Hodson, Ann; O'Hare, Anne (Journal of Speech, Language & Hearing Research, 2005)
Seventy-seven children between the ages of 6 and 10 years, with severe mixed receptive-expressive specific language impairment (SLI), participated in a randomized controlled trial (RCT) of Fast ForWord (FFW; Scientific Learning Corporation, 1997, 2001). FFW is a computer-based intervention for treating SLI using acoustically enhanced speech stimuli. These stimuli are modified to exaggerate their time and intensity properties as part of an adaptive training process. All children who participated in the RCT maintained their regular speech and language therapy and school regime throughout the trial. Standardized measures of receptive and expressive language were used to assess performance at baseline and to measure outcome from treatment at 9 weeks and 6 months. Children were allocated to 1 of 3 groups. Group A (n = 23) received the FFW intervention as a home-based therapy for 6 weeks. Group B (n = 27) received commercially available computer-based activities designed to promote language as a control for computer games exposure. Group C (n = 27) received no additional study intervention. Each group made significant gains in language scores, but there was no additional effect for either computer intervention. Thus, the findings from this RCT do not support the efficacy of FFW as an intervention for children with severe mixed receptive-expressive SLI. Reprinted by permission of the publisher.